Genetic and environmental influences on general knowledge and its relationship with intelligence - Bratko, Denis; Butković, Ana (2007)
It has been shown that measure of general knowledge correlates moderately with measures of intelligence (A. Furnham and T. Chamorro-Premuzic, 2006, Learning and Individual Differences, 16, 79-90 ; T. Chamorro-Premuzic, A. Furnham and P.L. Ackerman, 2006, Personality and Individual Differences, 41, 419-429), and that genes account for about half of the variance in intelligence (R. Plomin, 2003, in R. Plomin, J.C. DeFries, I.W. Craig and P. McGuffin, eds., Behavioral Genetics in the Postgenomic Era, American Psychological Association, Washington). The purpose of this study was to explore genetic and environmental influences on general knowledge and its relationship with intelligence. The sample consisted of 71 MZ and 78 DZ twin pairs, aged on average 17 years. General knowledge was measured with a test consisting of 60 items measuring different domains of general knowledge including geography, history, politics, art, science, fashion, sport. Four different measures of intelligence were used, two that measured spatial abilities (visualization and spatial orientation) and two that measured verbal abilities (word fluency and vocabulary). Univariate analyses indicated that the best fitting model for all measures includes additive genetic (A) and non-shared environmental (E) influences. Heritability estimates for intelligence measures were in the .60 to .77 range, while heritability of general knowledge was .91. Bivariate analyses between each of four intelligence measures as well as between composite intelligence score obtained as a factor score from four measures, and general knowledge measure were done using AE correlated factors model. Shared genetic influences were found between general knowledge and composite intelligence score (66%), visualization (43%), word fluency (53%) and vocabulary (78%). Some shared genetic influences were also found between general knowledge and spatial orientation (14%), but with zero included in the confidence interval.
Projekt MZOS
ENG